Congenital isolated adrenocorticotropic hormone deficiency in a newborn caused by TBX19 mutation: a case report and literature review - Dang, Yinxia; Zhang, Juanli; Wang, Fan (Frontiers in Pediatrics, 2024)
Background: To investigate the clinical phenotype, genetic characteristics, and prognosis of isolated adrenocorticotropic hormone deficiency in a newborn (IAD, OMIM 201400) caused by mutation of the TBX19 gene. Case Presentation: The clinical features, diagnosis, treatment, and prognosis of a newborn with IAD admitted to our hospital were retrospectively analyzed. The patient and his parents were also examined by whole exome sequencing. We used the terms "newborn", "child", "congenital isolated adrenocorticotropic hormone deficiency", and "TBX19" to retrieve relevant studies published up to December 2023 from the following databases: China National Knowledge Infrastructure (CNKI), Wanfang Database, Chinese Medical Journal Full-text Database, VIP database, Sinomed, PubMed, Embase, and Web of Science. The clinical and genetic characteristics of children from these other publications were summarized. The newborn boy with IAD was admitted to our hospital with poor mental response, feeding difficulties, hypoglycemia, and jaundice.The brain and adrenal MRI results were normal. Clinical whole exome sequencing showed that the boy carried compound heterozygous variants in the TBX19 gene.Specifically, the first exon had a novel frameshift mutation, c.240-246del(p.leu81Profs*54, NM_005149.3), and a missense mutation, c.377C>T(p.Pro126leu, NM_005149.3). The literature search found 34 additional cases from 4 Chinese-language articles and 12 English-language articles. The main clinical manifestations were hypoglycemia, jaundice, convulsions, feeding difficulties, poor mental response, hypotonia, and growth retardation. There were 24 cases with TBX19 mutations, and 19 different mutation sites. Among the 15 patients with different degrees of nervous system developmental delays, 13 initiated treatment when more than 1-year-old. Conclusion: IAD from TBX19 mutation causes nonspecific symptoms. Genetic testing is the key to diagnosis. Early diagnosis and treatment can help to improve the prognosis and prevent neurological complications.